The association between patients’ beliefs about medicines and adherence to drug treatment after stroke: a cross-sectional questionnaire survey - Sjölander, Maria (BMJ Publishing Group, 2013)
OBJECTIVES: Adherence to preventive drug treatment is a clinical problem and we hypothesised that patients’ beliefs about medicines and stroke are associated with adherence. The objective was to examine associations between beliefs of patients with stroke about stroke and drug treatment and their adherence to drug treatment. DESIGN: Cross-sectional questionnaire survey. SETTING: Patients with stroke from 25 Swedish hospitals were included. MEASUREMENTS: Questionnaires were sent to 989 patients to assess their perceptions about stroke (Brief Illness Perception Questionnaire, Brief IPQ), beliefs about medicines (Beliefs about Medicines Questionnaires, BMQ) and adherence to treatment (Medication Adherence Report Scale, MARS) 3 months after stroke onset. Only patients living at home were included in the analysis. The primary outcome was self-reported adherence as measured on MARS. MARS scores were dichotomised into adherent/non-adherent. Background and clinical data from the Swedish Stroke register were included. RESULTS: 811 patients were still living at home and 595 answered the questionnaire. Complete MARS data were available for 578 patients and 72 (12.5%) of these were classified as non-adherent. Non-adherent patients scored lower on positive beliefs as measured on BMQ-necessity (OR = 0.90, 95% CI 0.83 to 0.98) and BMQ-benefit (OR=0.77, 95% CI 0.68 to 0.87), and higher on negative beliefs as measured on BMQ-concern (OR=1.12, 95% CI 1.05 to 1.21), BMQ-overuse (OR=1.29, 95% CI 1.14 to 1.45), and BMQ-harm (OR=1.12, 95% CI 1.01 to 1.24). The Brief IPQ showed that non-adherent patients believed their current treatment to be less useful (p=0.001). CONCLUSIONS: This study showed associations between beliefs of Swedish patients with stroke about medicines and adherence. Positive beliefs were less common and negative more common among non-adherent. To improve adherence, patients’ beliefs about medicines should be considered.